The Rethinking Vocabulary Learning: The Power of English Movie Subtitles - Satria Rizki Pradana Suwandi; Khusnul Khatimah; Zulfa Nadia; Dzul Rachman (FKIP Unismuh Makassar, 2026)
Vocabulary mastery remains a persistent barrier in English as a Foreign Language (EFL) learning among senior high school students in East Kalimantan, particularly amid uneven educational resources. This study addresses the urgent need for accessible and context-sensitive strategies by examining the pedagogical potential of English movie subtitles. Employing a qualitative library research design, it synthesizes findings from academic literature, theses, and policy documents focusing on both urban and remote school contexts. The novelty of this study lies in its contextualized analysis of subtitle use across proficiency levels and infrastructural conditions. Findings indicate that subtitles enhance vocabulary acquisition through improved comprehension and lexical recognition. Intralingual subtitles benefit intermediate learners, while interlingual subtitles reduce anxiety among beginners. The study contributes practical insights into integrating audiovisual media in EFL instruction, highlighting the role of technological readiness and curriculum adaptability in optimizing learning outcomes.